Social Protection in Crisis: Evaluating BLT’s Role in Strengthening Household Resilience in Palu - Malizal, Zelydna Zeinab (Sinergi International Journal of Economics, 2025)
This study examines the effectiveness of Direct Cash Assistance (BLT) in improving the economic conditions of recipient communities in Palu City, Indonesia. In response to persistent urban poverty exacerbated by disasters and the COVID-19 pandemic, BLT has emerged as a key component of national social protection strategies. Using a descriptive quantitative design and data from 85 households across four administrative areas, the research employed a chi-square test to analyze the relationship between perceived program effectiveness and household economic outcomes. The findings reveal a statistically significant association (p = 0.023) between higher perceived BLT effectiveness and better reported economic conditions. Respondents who viewed the assistance as effective were more likely to report improved living standards, underscoring the program's role in mitigating economic vulnerability. The discussion highlights administrative factors, delivery mechanisms, and institutional frameworks as determinants of perceived and actual effectiveness. These results affirm the role of targeted cash transfers in supporting urban economic resilience, particularly in post-disaster contexts. The study contributes to ongoing debates on adaptive social protection and recommends further exploration into integrated policy designs for sustainable poverty reduction.